'Feeling the range': Emotional geographies of sound in prisons. (August 2016) - Hemsworth, Katie
Abstract: Sound, as a modality of emotion, is central to the everyday constitution of space. For an increasing population in Canada, however, incarceration forms the basis of everyday life. This paper explores the connections between sound and emotion as they play out in the under-researched context of prisons. I use a participant's term, "feeling the range, " to identify the atmospheric, haptic, and emotive potential of sound as a vital tool of spatial knowledge. These conceptualisations inform three findings that highlight the enabling and constraining complexities of aurality. First, sound and listening are epistemological practices that offer important tools for spatial orientation in otherwise restrictive environments; yet some materialities of sound, like reverberation, also cause great dis orientation. Secondly, the extensive capacities of sound enable connection with other beings and contexts during imprisonment; at the same time, sonic practices also dis connect, particularly through sonic techniques that carve out individualised auditory spaces. Finally, sound plays a crucial role in the enactment of power through resistance, and is used to reclaim dignity in undignified settings. This paper demonstrates that soundworlds can be as inclusive as they are exclusive, as convivial as they are hostile, and as therapeutic as they are torturous. Highlights: Prison inmates and staff employ affective listening to "feel the range". Sonic experiences of incarceration are both enabling and constraining. Sound is a spatializing tool that has orientating and disorientating effects in prisons. Sound connects and disconnects people and places in prisons. Sound is crucial in the negotiation of dignity in prisons.